Iki Putra Mubarrak v Kerajaan Negeri Selangor & Anor [2021] 3 CLJ 465 - Ali Mohamed, Ashgar Ali (CLJ Malaysia Sdn Bhd, 2025)
Section 28 of the Syariah Criminal Offences (Selangor) Enactment 1995, which criminalises unnatural sex, is in contravention of the State List in the Nineth Schedule of the Federal Constitution. The section, while providing for the offences against the 'precepts of Islam', is limited by the preclusion clause contained in the State List, ie, 'except in regard to matters included in the Federal List'. Criminal law being a federal matter, is exclusively for Parliament to enact; and is beyond the Legislative competency of the State Legislature.